Assessment in neuropsychology - Harding, Leonora, 1944-; Beech, John R. (Routledge assessment library., 1996)
Assessment in Neuropsychology is a practical and comprehensive handbook for neuropsychologists and other professionals who use neuropsychological tests in their everyday work. Each chapter outlines assessment procedures for specific functions such as language, visual impairment and memory. Case studies are used to illustrate their applications, pointing the professional towards the most relevant assessments for their clients' needs, and where and how they can be acquired. Leonora Harding and John R. Beech also explore new developments in neurological and neuropsychological assessment.